Young people's experiences in accessing sexual and reproductive health services in sub-Saharan Africa from 1994 to 2019 - A content analysis - Abubakari Sulemana Watara; Abu Mumuni; Yidana Zuwera; Apraku Anane Edward; Mutaru Goro Iddrisu; Badasu Delalali Margret (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2020)
Two and a half decades after the International Conference on Population and Development in 1994, access to Sexual and Reproductive Health (SRH) services by young people is very low, particularly in sub-Saharan Africa (SSA) despite the increasing resources being targeted at addressing the SRH needs of young people. This paper focuses on the needs and experiences of young people in accessing SRH services in SSA. Using a content analysis tool, this paper focused on review of published articles on barriers to SRH services, access and utilisation among young people in SSA from 1994 to 2019. Guided by the focus of the analysis, 21 studies out of 257 were finally selected, and findings presented from Burkina Faso, Ethiopia, Ghana, Kenya, Mali, Nigeria, South Africa, Tanzania, Uganda, Zambia, Democratic Republic of Congo and Zimbabwe. We found that unfriendly remarks by health providers; feeling embarrassed, shame and fear; limited information on SRH services; misconceptions about SRH services; lack of confidentiality and privacy are the major barriers to young people accessing SRH services. Addressing the negative attitude of health providers and the general misconceptions on SRH services are critical to improving SRH service utilisation among young people in SSA.